Different interactions between Tartary buckwheat protein and Tartary buckwheat phenols during extraction: Alterations in the conformation and antioxidant activity of protein. (30th August 2023) - Li, Dongze; Zhu, Ling; Wu, Qiming; Chen, Yiling; Wu, Gangcheng; Zhang, Hui
Highlights: Protein-phenol complexes were prepared at different extraction times. Phenols can bind to proteins by non-covalent/covalent interactions. The contribution rate of phenols to the antioxidant activity were studied. The structure of complex was changed by the binding of phenols. Abstract: The purpose of this study is to investigate the interaction between buckwheat protein and buckwheat phenols in the process of protein extraction and to compare the effects of phenols on protein structure and antioxidant activity. With the extension of extraction time, the content of total phenol increased from 150.51 to 336.01 mg gallic acid equivalent/g sample. Four phenols and seven phenols were identified by UPLC-Q/TOF-MS as binding to proteins in non-covalent and covalent forms, respectively. The contribution of non-covalent and covalent bound phenols to the antioxidant activity of the complexes were different. Meanwhile, the binding of phenols changed the infrared characteristic peak of protein, and reduced the fluorescence intensity and surface hydrophobic value. The free amino and sulfhydryl content of the protein decreased with increasing extraction time. These findings provide valuable information for one-step preparation of protein-phenol complexes.